Unraveling the promoting role of Fe in NiFe bimetallic catalysts for enhanced low-temperature CO2 methanation - Zhuoyi Yang; Ruwei Yao; Meng Yang; Han Zhang; Yueyin Song; Qinqin Niu; Congming Li (Chemical Engineering Journal, 2026)

Synergistic effect of fruit-vegetable powder and Staphylococcus on the physicochemical properties and microbial community of Yunnan dry-cured beef - Jiayan Tan; Qiongfang Yang; Guozhou Liao; Shuai Tang; Ruwei Ren; Yanfei Du; Jia Liu; Nannan Zhou; Wen Xun; Guiying Wang (International Journal of Gastronomy and Food Science, 2026)

Catalysis-inspired d-band center engineering enables hydrogen-suppressed zinc anodes for long-life aqueous zinc-ion batteries - Chunhui Gao; Zhenjing Jiang; Jie Chen; Kaining Zhang; Huijun Yang; Ruwei Chen; Hang Yang; Qingjin Fu; Zheng Li; Nana Xu; Mengran Wang; Bo Hong; et al. (Science Bulletin, 2026)

Analysis of intrinsic effects of compound curing agents on small molecule metabolites and microbial communities in Xuanwei ham based on metabolomics and high-throughput sequencing - Zhijie Zheng; Wenxi Fu; Guiying Wang; Bo Li; Wen Xun; Nannan Zhou; Chunfang Yang; Ruwei Ren; Shuai Tang; Yanfei Du; Jiayan Tan; Dahai Gu; et al. (Meat Science, 2025)

Tinosinenside A inhibits neuroinflammation and protects HT22 cells by suppressing the TLR4/NF-κB/NLRP3 signaling pathway in BV2 cells - Yongyan Xie; Yinfang Qin; Jingjing Wang; Ziwei Xu; Liping Chen; Yunxia Kuang; Ruwei Yang; Liping Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Revealing the effects of compound curing agents on the microbial community and metabolites of Nuodeng ham based on high-throughput sequencing and metabolomics - Zhijie Zheng; Mei Tian; Guiying Wang; Nannan Zhou; Wen Xun; Guanghui Chen; Ruwei Ren; Qiongfang Yang; Guozhou Liao (Food Chemistry, 2025)

Synergistic Na-S modified Fe-Cu catalysts for efficient CO2 hydrogenation to higher alcohols - Ruwei Yao; Yang Yu; Bin Wu; Yueyin Song; Qinqin Niu; Congming Li; Jian Wei; Qingjie Ge (Chemical Engineering Journal, 2025)

Unraveling compound curing agent on protein characteristics and proteome changes of Nuodeng ham by TMT-labeled quantitative proteomics - Nannan Zhou; Weicheng Kong; Guiying Wang; Wen Xun; Guanghui Chen; Ruwei Ren; Qiongfang Yang; Guozhou Liao (Food Chemistry, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

Establishing Virtual Bioequivalence and Clinically Relevant Specifications for Omeprazole Enteric-Coated Capsules by Incorporating Dissolution Data in PBPK Modeling - Ruwei Yang; Yaqi Lin; Kaifeng Chen; Jie Huang; Shuang Yang; An Yao; Xiaoyan Yang; Deqing Lei; Jing Xiao; Guoping Yang; Qi Pei (The AAPS Journal, 2024)

Mapping Chinese plastic flows from 2001 to 2040 based on dynamic probabilistic material flow analysis and scenario projection - Linlin Xia; Yuhan Ke; Zihao Wu; Jianbing Wang; Ruwei Wang; Yanpeng Cai; Zhifeng Yang (Resources, Conservation and Recycling, 2024)

Construction of a methodology framework to characterize dynamic full-sector land-use carbon emissions embodied in trade - Yuhan Ke; Linlin Xia; Ruwei Wang; Sai Liang; Zhifeng Yang (Science of The Total Environment, 2024)

China's economic restructuring reduced emissions of polycyclic aromatic hydrocarbons (PAHs) in the post-global financial crisis era - Linlin Xia; Jianbing Wang; Ruwei Wang; Sai Liang; Zhifeng Yang (Journal of Cleaner Production, 2024)

Distributed acoustic sensing for shallow structure imaging using mechanical noise: A case study in Guangzhou, China - Wenbin Jiang; Jiangnan Lin; Bin Liu; Ruwei Zhang; Baojin Zhang; Zhen Yang; Yuan Gu (Journal of Applied Geophysics, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Mutation Screening of the CHCHD10 Gene in Chinese Patients with Amyotrophic Lateral Sclerosis - QingQing Zhou; YongPing Chen; QianQian Wei; Bei Cao; Ying Wu; Bi Zhao; RuWei Ou; Jing Yang; XuePing Chen; Shinji Hadano; Hui-Fang Shang (Molecular Neurobiology, 2017)